DEFINING ORGANISATIONAL POLITICS - Karen Cacciattolo (European Scientific Journal, ESJ, 2014)
The paper discusses the type of political behaviour, mainly Mintzberg’s (1985) collection of games, Allen et al’s (1979) individual political tactics, and Lawrence et al’s (2005) types of power, as well as the causes of political behaviour. Some argue that politics are rooted in the wider configured environment (Gotsis & Kortezi, 2010: 498), while others argue that politics are a result of interpersonal antagonisms (Vince, 2001) or emotional matters (Vince, 2002). With regards to organisational politics, the literature presents various types of political behaviours, and research to date tackled the area of politics mostly in a purely theoretical manner. Moreover, studies presented to date have paid more attention to the general perceptions of politics rather than the observable political behaviours.